PENGARUH UKURAN PERUSAHAAN, AUDIT TENURE, AUDIT FEE DAN AUDIT DELAY TERHADAP KUALITAS AUDIT - Nope, Diana; Sudarmadi (Jurnal Nusa Akuntansi, 2024)
This research aims to determine the influence of Company Size, Audit Tenure, Audit Fee, and Audit Delay on Audit Quality in food and beverage companies listed on the Indonesia Stock Exchange in 2019-2023. This type of research is quantitative research and uses secondary data in the form of audited financial reports obtained from the official IDX website. The population in this study were 43 companies in the food and beverage sector listed on the Indonesia Stock Exchange in 2019-2023 with a sample selection technique using the purposive sampling method and 12 sample companies were obtained over a 5 year period so that the data analyzed amounted to 60 data. The analysis technique used is the Logistic Regression Analysis technique with the help of the eviews 12 program. The results of this research show that simultaneously Company Size, Audit Tenure, Audit Fee, and Audit Delay have no effect on Audit Quality. Partially, company size, audit tenure and audit delay have no effect on audit quality, while audit fees have a significant effect on audit quality.